The human species antigen on chromosome 11 - Buck, D; Bodmer, W (1975)
Immunization by human mouse cell hybrids of the mouse strain from which the parental mouse cell line is derived should lead to the production of antibodies directed specifically against the products (in particular, cell surface antigens) of genes on the human chromosomes in such hybrids. If a hybrid contains only one human chromosome, the assignment of a gene controlling a surface antigen identified in this way is immediate. Conversely, this approach should, in principle, be able to provide a set of genetic markers identifying the presence of each chromosome. If immunization is done with a hybrid containing more than one human chromosome, appropriate absorption with segregants can be used to purify sera so that they react with the gene products of only one chromosome. The authors used immunization with human mouse hybrids in this way to confirm the identification of a species antigen controlled by a gene linked to LDH A on chromosome 11.